Weighted single-step genome-wide association study identified genomic regions and candidate genes for growth and reproductive traits in Wenchang chicken - Ranran Zhu; Yu Zhang; Yuxiang Jiang; Zihan Xu; Yurong Tai; Ziyi Lian; Zhandeng Li; Xiuping Wang; Na Luo; Guiping Zhao; Xuemei Deng (Poultry Science)
Wenchang chicken is a native meat-type chicken breed in Hainan Province, China, known for its tender meat, which is in high demand both domestically and internationally. Improving important economic traits in Wenchang chicken is of significant importance to the poultry market. In this study, we genotyped 3737 individuals from two generations of Hainan Wenchang chicken using the Jingxin No. 1 55K SNP chip, and subsequently imputed the chip data. After quality control, 41,086 high-quality SNPs were obtained. We performed weighted single-step genome-wide association study (wssGWAS) on six traits using a single-trait model, and searched for candidate genes within QTL regions explaining more than 1 % of the genetic variance. Based on the contribution to genetic variation from QTL regions, we identified 4, 8, 5, 6, 9, and 8 candidate regions for EP, 35w-EW, BW, FT, SL, and AFE, respectively. The top three significant windows cumulatively explained 5.03 %, 5.18 %, 19.05 %, 5.87 %, 6.15 %, and 3.86 % of the genetic variation for these traits, respectively. Within these regions, we identified 14 genes, including LDB2 and GIT1, which had previously been reported to be associated with ovarian development, body weight, and fat differentiation. The biological processes and pathways involving these genes include cartilage development, lipid molecule synthesis and metabolism, angiogenesis, and cell proliferation and migration. LDB2 was proposed as a strong candidate gene due to its significant function and high consistency with other studies regarding various carcass traits in chickens. Our findings provide valuable information for broiler breeding based on molecular selection.